Development of a power - operated coconut husking machine - ANU S. CHANDRAN ANEESH MOHAN SHABEENA P.K; Er. Jippu Jacob (Guide) (Tavanur 2009 Kelappaji College of Agricultural Engineering and Technology)
Development of a power - operated coconut husking machine
Development of a power - operated coconut husking machine